HUBUNGAN TINGKAT KECEMASAN DENGAN KUALITAS TIDUR PADA PASIEN GAGAL JANTUNG KONGESTIF(CHF) - Mitia Eka Wati, Zela; Oktarina, Yosi; Rudini, Dini (Jurnal Ilmiah Ners Indonesia, 2020)
Almost all patients realize that the cardiovascular system is a very important part. When the heart begins to break down and its manifestations deteriorate, health will be threatened. In patients with heart failure an increase in manifestations can cause fear so that patients will express their fears in various ways including anxiety. This excessive anxiety will have an impact on poor sleep quality. This study aims to determine the relationship between anxiety level and sleep quality in CHF patients in the heart clinic at Raden Mattaher Hospital Jambi. This research a quantitative study a cross sectional approach. The sampling technique was purposive sampling (n = 73). The statistical test used is the Spearman correlation test where this correlation is used to measure the relationship between two variables and find out the direction of the relationship. The instrument used in this study was  quesionare PSQI (r = 0.741) to assess sleep quality and quesionare GAD-7 (r = 0.83) to assess anxiety levels. The results of this study showed the majority of respondents had mild anxiety as many as 35 people (47.9%) and poor sleep quality as many as 47 people (64.4%). The results of the Spearman rank test analysis p value = 0.004 <0.05, then there is a relationship between the level of anxiety and the quality of sleep. There is a relationship between anxiety level and sleep quality in CHF patients. For further research, it is expected to be able to use the results of the study as basic data in carrying out further research